Medical and Dental Students Attitudes toward Their Study Field before and after Experiencing Clinical Practice in Kerman University of Medical Sciences Iran - Esmat Noohi; Ali Akbar Haghdoost; Ali Akbar Haghdoost; Afsaneh Mohammadi (Kerman University of Medical Sciences, 2015)
Background & Objective: Learning environment should be opportunities for positive change in students attitude to encourage them and create more interest leading to sustainable learning To make constructive changes having information on the current status and about students attitudes toward their discipline is essential This study was designed to assess the medical and dental students attitude toward their study field (learning environment practicability attraction social rank and future employment) before and after experiencing clinical practice in Kerman University of Medical Sciences Iran Methods: This crosssectional analytic study was conducted in 2012 The study population were 95 medical and dental students of Kerman University of Medical Sciences as census of students A researchermade questionnaire was designed consisting 33 questions in five areas of the components of medical education and health care (education environment applicability of the course the attractiveness of the field career and social status) Data were analyzed using paired t ANOVA and MannWhitney U tests via SPSS software Results: There were significant differences between the medical students attitude toward educational environment and practicability of the field before and after experiencing clinical practice but there was no significant difference between their attitude toward attraction future employment and social rank of the field On the other hand there were significant differences between dental students attitudes toward educational environment and future employment before and after experiencing clinical practice but there was no significant difference between their attitudes toward practicability attraction and social rank of the field In addition there was no significant difference between the two groups based on gender and age Conclusion: The results showed significant differences only in three educational components between two groups of students According to obtained data short and longtime plans could be designed for increasing the efficiency of education improving educational structure and obtaining welfare and economical possibilities for students